Magma evolution in the Halls Creek Orogen; insight from geodynamic numerical modelling and geochemical analysis. Issue 1 (1st December 2018) - Kohanpour, Fariba; Kirkland, Christopher; Gorczyk, Weronika; Occhipinti, Sandra; Lindsay, Mark
Abstract : In this work two plausible tectonic scenarios for the Halls Creek Orogen are examined using a 2D thermo-mechanical-petrological numerical experiment based on I2VIS code. The initial constraints for the model setup are appropriate to the inferred tectonic environment for the protoliths to the Tickalara Metamorphics in an intra-ocean subduction or ocean-continent subduction/collision. These numerical models allowed us to examine a range of conceptual models for the different geodynamic settings for the Halls Creek Orogen through time. With this approach, we determined experiments with specific physical parameters that are compatible with the geology observed in the Halls Creek Orogen. Finding the model most compatible with observed geology can help to reveal geological processes which are not observable without the aid of geodynamic simulation. The results indicate that the geology of the Halls Creek Orogen is best represented by the ensialic marginal basin scenario. A further aspect of the numerical models is the degree to which they reveal magmatic activities which lead to the generation of key lithological units during the tectonic evolution of the Halls Creek Orogen. Development and closure of a marginal basin and the role of collisional magmatism are important parts of tectono-thermal evolution of the Halls Creek Orogen. The numerical models predict magma sources through time, linked to the tectonothermal evolution of the region. Hf-isotopic evolution patterns from the region have been used to verify and improve the models as this isotopic system is able to chart the influence of crust and mantle in melts through time. Lu-Hf data from zircon grains indicate a substantial juvenile melt addition in c. 1865-1840 Ma linked to marginal basin development in the Halls Creek Orogen.